DESENVOLVIMENTO E APLICAÇÃO DE SOFTWARE PARA ANÁLISE DA ESTRUTURA E DINÂMICA EM FLORESTAS NATURAIS - Gardin, Edson (2011)
The Analysis System Dynamics and Structure of Natural Forests (SADEF) is a program that was designed to permanently store the measurements taken in forest inventories, process them and generate the information of the horizontal structure, vertical structure, using the diagram h-M; indices similarity and diversity (Shannon-Weaver and Simpson diversity, Pielou`s uniformity, Berger-Parker, Jaccard similarity); Morisita index of dispersion, the dynamics of growth with the use of transition matrix and the balanced structure of the forest using the Meyer’s equation. The SADEF was designed to be multi-user environment and operate in a computer network. Using SADEF and data collected from 2001-2009, in a fragment of Ombrophyllous Mixed Forest, belonging to the National Forest of São Francisco de Paula in the state of Rio Grande do Sul, was performed analysis of the structure and forest dynamics. The evaluations were referring to floristic composition, horizontal and vertical structure, the spatial distribution of the tree component, the dynamics of growth and diameter distribution. The area studied had high species richness, with uniform medium in which few species are predominant in the community, mainly characterized by the occurrence of Araucaria angustifolia and with an increase, particularly since 2006, of Casearia decandra. Regarding the dynamics of growth, using the transition matrix as a method of prognosis, the results show no significant difference between the total number of trees observed and estimated, however there were significant differences for the prognose of mortality by diameter class between observed and estimated. Confirming that the transition matrix method is a tool to serve the purposes of estimates of forest dynamics. To analyze the structure diameter, which were adjusted as a function of the center of class by the Meyer's equation, the analysis of data shows that the forest is not yet in equilibrium. This disequilibrium in the frequencies of each diameter class occurs mainly in the larger DBH classes, which may have been caused by selective logging of some species.